Working Characteristics of the Scroll Expander for Residual Pressure Recovery in Microscale Gas Pipeline Networks - Yanqin Mao; Liang Cai; Roman Chertovskih; Jiahong Ji; Shen Su (Machines)
A widespread distribution of gas-regulating stations creates challenges in energy recovery during pressure reduction. This study employs a scroll expander as a central mechanism to enhance the efficiency of residual gas pressure recovery, demonstrating its adaptability. We conducted experimental tests on its power generation capabilities and numerically studied the expansion characteristics. Our results indicate significant improvements as the inlet pressure was increased from 85 kPa to 375 kPa: the generator speed increased from 1238 rpm to 4615 rpm, the power output increased from 9.64 W to 165.48 W, and the temperature difference between the inlet and outlet flows changed from 5.41 K to 27.3 K. Turbulent dissipative and wall friction were identified as primary contributors to the energy loss, overcoming the temperature and viscosity loss, and increasing together with the radial and axial clearances. A comparative analysis of scroll designs reveals that the scrolls modified with higher order and arc curves display a reduced torque compared with the traditional circular involutes, and more scrolls are beneficial for handling high-pressure gas. These findings offer insights into scroll expander design, enhancing the energy efficiency of microscale gas residual pressure recovery systems.